Cupping Therapy Approach as a Nonpharmacological Strategy for Controlling Headaches in Outpatients - Yanti, Rahmatul Fithri; Babeker, Mohamed M (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: Headache is a highly prevalent neurological complaint commonly managed with pharmacological therapy, which may cause adverse effects with long-term use. This study aimed to evaluate the effectiveness of cupping therapy as a nonpharmacological strategy for controlling headache among outpatients. Methodology: A quasi-experimental one-group pretest–posttest design was employed involving 16 outpatients with headache. Pain intensity was measured before and after cupping therapy using the Visual Analog Scale (VAS). Data were analyzed using the Shapiro–Wilk normality test followed by paired sample t-test with a significance level of p < 0.05. Main Findings: The mean VAS score significantly decreased from 6.75 ± 1.29 before intervention to 3.12 ± 1.15 after intervention, with a mean reduction of 3.63 points (t = 14.21; p < 0.001). Severe pain prevalence declined from 56.2% to 6.2% following therapy. These findings indicate that cupping therapy effectively reduces headache pain intensity in outpatient settings. Novelty/Originality of this study: This study positions cupping therapy as an evidence-informed nonpharmacological intervention within structured outpatient healthcare services, quantitatively bridging traditional therapeutic practice with modern clinical evaluation using standardized pain measurement and statistical validation.